Structural analyses of blended Nafion/PVDF electrospun nanofibers. Issue 20 (10th May 2019) - Nawn, G.; Vezzù, K.; Negro, E.; Pace, G.; Park, J. W.; Wycisk, R.; Cavinato, G.; Pintauro, P. N.; Di Noto, V.
Abstract : A new type of polymer blend, prepared by electrospinning nanofibers containing the immiscible polymer polyvinylidene fluoride (PVDF, 10 wt%) and Nafion® perfluorosulfonic acid (90 wt%), has been characterized experimentally. Abstract : A new type of polymer blend, prepared by electrospinning nanofibers containing the immiscible polymers polyvinylidene fluoride (PVDF, 10 wt%) and Nafion® perfluorosulfonic acid (90 wt%), has been characterized experimentally. The internal nanofiber morphology is unique and unlike a normal blend, with individual phase-separated and randomly distributed fibrils of Nafion and PVDF (∼2–7 nm in diameter) that are bundled together and aligned in the fiber axis direction (where the fiber diameter is ∼500 nm). This morphology is retained when fiber mats are hot-pressed into dense films. The physicochemical properties of the electrospun blended fibers are also highly unusual and unanticipated. As shown in this study, each polymer component influences the thermal and structural behavior of the other, especially in the dry state. Thus, dry composite polymer mats and membranes exhibit properties and attributes that are not observed for either pure PVDF or pure Nafion. Experimental results indicate that: (i) PVDF imparts conformational constraints on the polytetrafluoroethylene (PTFE) backbone chains of Nafion, resulting in an increased 21 helical conformation that effects Nafion's water uptake and thermal properties; and (ii) dipole–dipole interactions between PVDF polymer chains and Nafion make the β-phase polymorph of PVDF much more stable at elevated temperatures. Such "reciprocal templating" in electrospun fibers may not be unique to Nafion and PVDF, thus the procedure represents a new method of creating nanostructured multi-component polymer materials with innovative features.